KONTRIBUSI HASAN HANAFI DALAM KAJIAN USHUL FIQH - Mashduqi, Muhammad Anis (UIN Sunan Kalijaga Yogyakarta, 2012)
Hasan Hanafi is an expert on Islamic law who had the idea of reconstruction usul fiqh. Min Al-Nash ila Al-Waqi, written by him as the reconstruction effort, continuing the spirit of creativity, Al-Risala, Al-Mushtashfā and Al-Muwāfaqāt. Min Al-Nash ila Al-Waqi' written to undermine the claims of Islamic law to disappear the public good (al-mashāliħ al-' ammah). The entire reconstruction project of Hanafi had been referred as a result of application of the phenomenological method. Hanafi called tahlil manhaj al-khabarāt, comparable to manāhij al-ta'wil, manāhij al-nazhar, manāhij al-żauq, manāhij al-tahlil al-lughawī and other methods of classical Islamic creations. Through the philosophy of phenomenology, hermeneutics Gadamerian, Hanafi appreciate the application of the themes and traditions of thought, but in the context of Al-Quran and Al-Sunnah. Hanafi recommends usul fiqh as sacra hermeneutica, the specific case of general hermeneutics. Hanafi, divides methodological-epistemological consciousness of usul fiqh into three-dimensional consciousness; historical consciousness (la conscience historique), eidetic consciousness (la conscience eidetique), and the active awareness (la conscience active). Hanafi finds methodological shift that can be read from configuration changes chapter and logical structure of usul fiqh texts shift. This changes was seen in Al-Mustashfa, work of al-Ghazali (d. 505 H) and Al-Muwāfaqā,t work of Al-Syatibi (d. 790 H).